TAKING CARE OF THE PERSON WHO TAKES CARE: REFLECTIONS ABOUT THE LEARNING OF THIS SKILL - Karina Machado Siqueira; Denize Bouttelet Munari; Keyti Cristine Alves Damas (Universidade Federal de Goias, 2004)
This article makes a reflexive analysis under the view of the nursing´s student about the needing ofdirect care of the person who takes care of the patient for this can assist the client in a humanized way. It´s writenabout the meaning of care and its use in Nursing including for those who are cared and for those who takes care. Itsuggests that interventions must be made in the nursing graduation process. These interventions have the purposeto develop the perception that the attention dedicated to the other must be equal to the one dedicated to yourself.